ANALISIS PENGARUH SUBSTITUSI BAN BEKAS TERHADAP STABILITAS DAN KEPADATAN ASPAL AC-WC - Rosyad, Farlin; Sapitri, Sinta Bela (Rang Teknik Journal, 2024)
Theautomotiveindustryincreasesalongwiththeincreaseintireproductionwhichresultsinan increaseintirerubberwastethatcannotbeattributedtonaturalfactors.Intuitivewaystosolvethisproblem, innovativewaysareneededtoreducetirerubberwastewhichisincreasingly increasing. Theuseoftire rubberasasubstitute-increasing materialforasphaltisoneoftheintuitivewaystoreduceunusedtire rubberwaste. Itishopedthatasphaltmixedwith rubbertirepieces canactasasubstitute forsimilar materialsandthestabilityoftheasphaltwillincrease.Usedtire rubberwasteisveryeasy tofind,butthis materialisdifficulttofindnaturally.This aims toinvestigatetheimpact of replacingconventionalcoarse aggregatewithusedtirepowderonthestability anddensity oftheAC-WC asphaltmixture.Wastetire powder,which isarecycledproductfrom usedtires,isusedasanadditive inasphaltmixtures toreduce theuseof naturalaggregatesandsupportsustainablerecyclingpracticesintheroadconstructionindustry. Theresearchmethodinvolvesthepreparation ofseveralAC-WCasphaltmixtureswithvaryingratiosof usedtirepowder.Theresultingasphaltmixtureisthentestedusingvariouslaboratory tests,including stabilityand densitytests.Inaddition,analysisofmechanicalpropertiessuchasmodulusofelasticityand tensilestrengthwasalsocarriedouttoevaluatetheperformance ofasphaltmixturescontainingusedtire powder.Basedonthe resultsofMarshallparametertestingintermsofvariationsinused tire substitution, itcanbeconcludedthattheinfluenceofthestabilityvalueonoptimumtirerubberisatapercentageof4% witha valueof1,846kg.Meanwhile,basedonthetestresultsintermsofvariationsinusedtires,itcanbe concludedthattheinfluenceofdensityvalueonoptimumtirerubberisatapercentageof4%witha value of2.377gr/cc.